2008
DOI: 10.1073/pnas.0710351105
|View full text |Cite
|
Sign up to set email alerts
|

PDC-TREM, a plasmacytoid dendritic cell-specific receptor, is responsible for augmented production of type I interferon

Abstract: Type I interferons (IFNs) derived from plasmacytoid dendritic cells (PDCs) are critical for antiviral responses; however, the mechanisms underlying their production remain unclear. We have identified a receptor, PDC-TREM, which is associated with Plexin-A1 (PlxnA1) on the PDC cell surface and is preferentially expressed after TLR-stimulation. Limited TLR signals induced PDC-TREM expression but failed to induce IFN-α production. However, when coupled with Sema6D, a ligand for Plexin-A1, limited TLR-stimulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
83
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(83 citation statements)
references
References 46 publications
(46 reference statements)
0
83
0
Order By: Relevance
“…42,57 In the immune system, plexin-A1 is specifically expressed in DCs, where it mediates the activation of T cells and the production of type I interferon. 20,58,59 The generation of antigen-specific T cells is impaired in plexin-A1 2/2 mice. 20 Sema6D, which is expressed in T cells, B cell and natural killer cells, was identified as a putative ligand for plexin-A1.…”
Section: Regulation Of Immune Cell Responses H Takamatsu Et Al 84mentioning
confidence: 99%
See 1 more Smart Citation
“…42,57 In the immune system, plexin-A1 is specifically expressed in DCs, where it mediates the activation of T cells and the production of type I interferon. 20,58,59 The generation of antigen-specific T cells is impaired in plexin-A1 2/2 mice. 20 Sema6D, which is expressed in T cells, B cell and natural killer cells, was identified as a putative ligand for plexin-A1.…”
Section: Regulation Of Immune Cell Responses H Takamatsu Et Al 84mentioning
confidence: 99%
“…Plexin-A1 forms a receptor complex with the TREM family of proteins and the adaptor molecule DAP12. 20,58 Both DAP12-deficient and plexin-A1-deficient mice not …”
Section: Regulation Of Immune Cell Responses H Takamatsu Et Al 84mentioning
confidence: 99%
“…GM-CSFR␣-Ig was purified from the culture supernatants of transfected HEK293 cells using a protein A-Sepharose column as previously described 32 (GE Healthcare; supplemental Figure 1A). Anti-GM-CSFR␣ monoclonal antibody (mAb; 3A6D1) was developed by immunization of Wister rats with GM-CSFR␣-Ig.…”
Section: Generation Of Anti-gm-csfr␣ Mabmentioning
confidence: 99%
“…Based on these observations, we postulated that T cells express a Sema protein that interacts with Plxna1 in a simple ligandreceptor pairing. However, recent publications have revealed that similar to the TNF, CD28, and B7 families, immune cells express numerous Sema and Plex ligand-receptor pairs with multiple proteins interacting within a functional group (8)(9)(10)(11)(12). For example, during DC and T cell interactions, combinations of the following known receptor-ligand pairs are expressed: Plxna1-Sema3A, Sema3A-Plxna4, Plxna1-Sema6D, and Plxna4-Sema6D.…”
mentioning
confidence: 99%
“…Moreover, the expression patterns also suggest the potential for homotypic pairings during T cell-T cell contact or DC-DC contact. Finally, the identification of Sema and Plex expression by multiple immune cell types increases the potential for complex cell-cell interactions beyond a simple DC and T cell model of regulation (11,13). The multivariate interactions of Sema and Plex proteins are difficult to characterize, especially given that the majority of functional studies have relied on knockout mice with potential developmental disruptions in which multiple tissues, interactions, cell types, and maturation states may be affected (12).…”
mentioning
confidence: 99%